Indonesian Learners’ Motivation in English Reading Classroom - Reni Kusumaningputri (Universitas Bunda Mulia, 2017)
This study presents results on learners’ motivation in English reading classroom where English is a foreign language. Motivation is seen to have two categories; intrinsic and extrinsic motivation. Seven constructs comprising motivation are sought and explained through questionnaire and interview. Some interesting findings are that in classroom context, when learners read, it is meant to be an assignment not a necessity. Friends hold an important motivational trigger to arouse and further arguably maintain willingness to read. Meanwhile teachers are potentially considered to arouse extrinsic motivation making teachers need to create such atmosphere to spark intrinsic motivation through classroom activities. Keywords: intrinsic motivation, extrinsic motivation, L2 reading